Fenomena Kelompok Keagamaan Baru (Heresy) Dalam Islam - Mukhtar Hadi (Ri'ayah: Jurnal Sosial dan Keagamaan, 2017)
Today religious social discourse is faced with the emergence of several denominations either reactualizing the old reborn groups or really new groups. This phenomenon is interesting to understand because the birth of these groups raises various problems in inter-religious and government relations. Another issue is related to the protection of minority rights that will continue to coincide with reactions that arise to new symptoms of religious expression or the phenomenon of this splinter flow. As far as observations can be made, there is a tendency for reactions to the emergence of new flows that have triggered communal conflicts in various regions. This study aims to determine the factors that encourage the birth and development of the Ittiba'al-Salaf group, to know the characteristics of the group Ittiba 'al-Salaf, and the to know the religious ideology of the group Ittiba' al-Salaf. Based on the process of collecting and analyzing the data, it is concluded that Ittiba 'al-Salaf is a group of variants of Jamaah Salafi who aspires to carry out life in the field of religion and society as exemplified by the generation of salaf, the generation after the death of the Prophet : sahabah, tabi'in, and tabi'ut tabi'in. This Jamaat demands the authenticity of Islamic teachings that are considered to have undergone changes and additions by Muslims. Thus this is a congregation with the spirit of purification of religious teachings or puritanism. Another factor is the response or resistance to the social life of Muslims who are considered more concerned with the way of life that is not based on Islamic teachings but instead imitate the ways of life of other people (tasyabbuh). Jamaat Ittiba 'al-Salaf is not a particular group of madzab or an organization. They call themselves true Muslims, those who hold true Islam according to the Sunnah of Prophet SAW, followers of manhaj nubuwwah and manhaj salaf. Ittiba 'al-Salaf religious beliefs are inseparable from puritanism, where their understanding of aqidah, worship and muamalah rests on the textual basis of Islamic shari'a that denies both tafsir and ta'wil based on rationality